A comprehensive exploration of groundwater governance challenges and solutions - N, Yamuna; Nayak, Mahantesh R; N, Rakesh (Indian Farming, 2024)
Groundwater, comprising 97% of accessible freshwater, is vital for over two billion people, supporting agriculture, industry, and domestic use. Despite its critical role, over-extraction and pollution threaten its sustainability, particularly in India, the world's largest groundwater user. Effective governance is hindered by legal ambiguities, inadequate enforcement, and unsustainable practices. Solutions lie in transparent regulations, participatory management, and innovative approaches like the Jyotigram Scheme in Gujarat. Global examples, including Integrated Water Resource Management, underscore the need for coordinated efforts. Urgent action frompolicymakers, communities, and stakeholders is essential to safeguard this invaluable resource for future generations.